2007
DOI: 10.1111/j.1469-7580.2007.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive diversity of incisor enamel microstructure in South American burrowing rodents (family Ctenomyidae, Caviomorpha)

Abstract: The aim of this study was to analyse the morphofunctional and adaptive significance of variation in the upper incisor enamel microstructure of South American burrowing ctenomyids and other octodontoid taxa. We studied the specialized subterranean tooth-digger † Eucelophorus chapalmalensis (Pliocene -Middle Pleistocene), and compared it with other fossil and living ctenomyids with disparate digging adaptations, two fossorial octodontids and one arboreal echimyid. Morphofunctionally significant enamel traits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 28 publications
1
31
0
6
Order By: Relevance
“…; Martin, ; Vieytes et al. ), but by far the greatest differences were reported by Moinichen et al. () relative to positional location of rows across the thickness of the inner enamel layer, that is, a decussation angle in mandibular mouse incisors of 30° near the DEJ, an angle of 60° in the middle portion of the inner enamel layer, and a decussation angle of 80° near the boundary of inner and outer enamel layers.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…; Martin, ; Vieytes et al. ), but by far the greatest differences were reported by Moinichen et al. () relative to positional location of rows across the thickness of the inner enamel layer, that is, a decussation angle in mandibular mouse incisors of 30° near the DEJ, an angle of 60° in the middle portion of the inner enamel layer, and a decussation angle of 80° near the boundary of inner and outer enamel layers.…”
Section: Discussionmentioning
confidence: 94%
“…There has been considerable disagreement in the literature regarding the angle at which the alternating rows of rods cross one another traveling in either a mesial or lateral direction across the thickness of the inner enamel layer in rat and mouse incisors, from as little as 30° (Moinichen et al 1996) to as much as 90° (Warshawsky, 1971). As with rod incisal tilt angle, differences by species and tooth type have been noted for decussation angles in mandibular mouse incisors (Von Koenigswald, 1985;Moinichen et al 1996;Martin, 1999;Vieytes et al 2007), but by far the greatest differences were reported by Moinichen et al (1996) relative to positional location of rows across the thickness of the inner enamel layer, that is, a decussation angle in mandibular mouse incisors of 30°near the DEJ, an angle of 60°in the middle portion of the inner enamel layer, and a decussation angle of 80°near the boundary of inner and outer enamel layers. The average decussation angle observed in this study based on grand means for row tilts (Figs 4B and 8A) was comparable to a grand mean that can be computed from the range of decussation angles reported by Moinichen et al (1996): 104°À 49°= 55°vs.…”
Section: Rod Decussation Anglementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the mandibular apparatus of these rodents has been able to promote an equivalent evolutionary diversification as well. Many published analyzes on Caviomorpha support our findings, especially, by describing the morphological diversification of cranial, mandibular, and dental traits (e.g., angular process' size, zygomatic width, dental procumbency, molariforms' microstructure), and linking them to their different ecological niches, diets, social and locomotor skills, and functional potentialities, for example, for the subterranean lifestyle (see, e.g., Vassallo, '98;Fernández et al, 2000;Bacigalupe et al, 2002;Verzi, 2002;Mora et al, 2003;Mardegan Issa et al, 2007;Vieytes et al, 2007;Lessa et al, 2008;Álvarez et al, 2011). So, changes in the performance of biting force would allow the mandibular apparatus to be involved in some other behaviors (e.g., digging) beyond the strictly trophic one, which in the case of Ctenomys is closely linked to the occupation of a distinctive ecological niche.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers within circles internal to each node indicate relative Bremer support values resulting from evolution of 800 trees up to 31 steps longer than the optimum. (Fernández et al 2000;Verzi and Olivares 2006;Vieytes et al 2007;Lessa et al 2008;Verzi 2008).…”
Section: Article In Pressmentioning
confidence: 98%